Mechanism for Implementing Land and Building Tax Distribution in Realizing Revenue Autonomy Areas in DKI Jakarta - Baiquni, Adi; Mustomi, Otom (International Journal of Educational Research & Social Sciences, 2023)
Mechanism for Implementing Land and Building Tax Collection in Realizing Regional Revenue Autonomy in DKI Jakarta. First, the purpose of the study, to describe and analyze and explain the implementation of the withdrawal of Land and Building Tax (PBB) arrangements in the Province in DKI Jakarta and the objections that can be made by taxpayers to the APBD. To elaborate and analyze and explain the implementation of Land and Building Tax (PBB) collection to realize regional autonomy in DKI Jakarta.Second, the scope of research of the Daerh Government's authority in carrying out the collection of Land and Building Tax in DKI Jakarta regarding the scope of this research includes Land and Building Tax. The third research method is to use qualitative research methods that are normative. Fourth, the results of research that discusses the authority of the Regional Government in collecting regional Land and Building Taxes have been determined by applicable laws and regulations, in the 2022 fiscal year Revenue from the UN Reaches 25% of the Total Tax DKI The DKI Jakarta Provincial Government receives the largest tax income from the Land and Building Tax (PBB). The value reached Rp.6.32 trillion. If detailed, the figure is equivalent to a quarter of the total value of taxes that can be collected. of the admission plan. Meanwhile, the plan to collect Land and Building Tax in the 2023 fiscal year is for the DKI Jakarta Government. Fifth, Conclusion Local Original Revenue is a source of finance extracted from the relevant regional area, therefore in order to be able to finance the implementation of regional government, regions are authorized to regulate their households including increasing local original revenue from taxes and levies, especially the Land and Building Tax (PBB) of the DKI Jakarta Regional Government in practice increases Regional Original Revenue from the Land and Building Tax sector.